Bond strength of different endodontic sealers to dentin: Push-out test - Barbizam, João Vicente Baroni; Trope, Martin; Tanomaru-Filho, Mario [UNESP]; Teixeira, Erica Cappelletto Nogueira; Teixeira, Fabricio Batista (FapUNIFESP (SciELO), 2011)
Objective: The aim of this in vitro study was to evaluate the bond strength of different root canal sealers to dentin. Material and Methods: Forty extracted single-rooted human teeth were examined and the coronal and middle thirds of the canals were prepared with a 1.50 mm post drill (FibreKor Post System, Pentron). The teeth were allocated in two experimental groups, irrigated with 2.5% NaOCI + 17% EDTA or saline solution (control group) and instrumented using Race rotary files (FKG) to a size #40 at the working length. Then, the groups were divided into four subgroups and filled with Epiphany sealer (Group 1), EndoREZ (Group 2), AH26 (Group 3) and Grossman's Sealer (Group 4). After 2 weeks of storage in 100% humidity at 37°C, all teeth were sectioned transversally into 2-mm-thick discs. Push-out tests were performed at a cross-head speed of 1 mm/min using a universal testing machine. The maximum load at failure was recorded and expressed in MPa. Results: Means (±SD) in root canals irrigated with 2.5% NaOCI and 17% EDTA were: Gl (21.6±6.0), G2 (15.2±3.7), G3 (14.6±4.5) and G4 (11.7±4.1).Two-way ANOVA and Tukey's test showed the highest bond strength for the Epiphany's group (p< 0.01) when compared to the other tested sealers. Saline solution decreased the values of bond-strength (p<0.05) for all sealers. Conclusion: Epiphany sealer presented higher bond strength values to dentin in both irrigating protocols, and the use of 2.5% NaOCl and 17% EDTA increased the bond strength values for all sealers.
Keywords: Push-out; Root canal filling material; Root canal obturation